20.0k views
2 votes
-3(8)+5y=-24 using elimination ​

-3(8)+5y=-24 using elimination ​-example-1

2 Answers

2 votes


\bold{Answer}


\boxed{\bold{Y \ = \ 0}}


\bold{Explanation}


  • \bold{Solve: \ -3\left(8\right)+5y=-24}


\bold{------------------}


  • \bold{Remove \ Parenthesis \ (a) \ = \ a}


\bold{-3\cdot \:8+5y=-24}


  • \bold{Multiply \ Numbers: \ 3\cdot \:8=24}


\bold{-24+5y=-2}


  • \bold{Add \ 24 \ To \ Both \ Sides}


\bold{-24+5y=-2}


  • \bold{Simplify}


\bold{5y=0}


  • \bold{Divide \ Both \ Sides \ By \ 5}


\bold{(5y)/(5)=(0)/(5)}


  • \bold{Simplify}


\bold{Y \ = \ 0}


\boxed{\bold{Eclipsed}}

User Lysette
by
4.9k points
0 votes

Answer:

y=0

Explanation:

-3(8) + 5y = -24

-24 + 5y = -24

y=0

User Ku
by
5.7k points